Electronic structure and dielectric properties of ZrO2-CeO2 mixed oxides. (August 2018) - Varshney, Mayora; Sharma, Aditya; Chae, Keun Hwa; Kumar, Shalendra; Won, Sung Ok
Abstract: ZrO2 –CeO2 mixed ceramics were studied for their local electronic structure and dielectric properties. X-ray diffraction (XRD), scanning electron microscope (SEM), X-ray absorption fine structure (XAFS) and frequency dependence dielectric constant measurements were performed on the samples. Rietveld refinements and quantitative phase analysis of ZrO2 -CeO2 ceramics showed an increased concentration of tetragonal ZrO2 and cubic Zr0.5 Ce0.5 O2 phases at the expense of parent monoclinic ZrO2 . The morphology of the ZrO2 -CeO2 ceramics remained invariant for all of the fractional percentages of CeO2 loading. O K-edge and Ce M5, 4 -edge NEXAFS showed the oxygen vacancies and Ce 3+ -Ce 4+ redox pair formation in ZrO2 CeO2 ceramics, which is further corroborated by Ce L3 -edge XAFS. The higher CeO2 molar ratios containing ZrO2 –CeO2 ceramics showed higher ε′, ε″ and σac and lower tan δ. Graphical abstract: Highlights: ZrO2 -CeO2 mixed ceramics were prepared using a solid-state reaction technique. XRD, FE-SEM, XAFS and frequency-dependent dielectric-constant measurements were performed. O K-edge, Ce M5, 4 -edge and Ce L3 -edge XANES have confirmed Ce 3+ and Ce 4+ redox pairs. ZrO2 -CeO2 ceramics have shown higher ε′, ε″ and σ ac and lower tan δ as a function of frequency.